Analisis Pengaruh Kualitas Produk, Pelayanan, Harga, dan Promosi Pada Rumah Makan Star Steak di Karanganyar - Utomo, Sony Febri (2016)
This study has the objective to analyze the influence of variables Product Quality, Service, Price and Promotion of the purchasing decision and determine whether the product quality able to explain better purchasing decisions when compared Services, Price and Promotion. This research is descriptive quantitative questionnaire as a data collection tool that is analyzed using data processing software SPSS for Windows version 22. The samples were carried out using non-probability sampling through accidental sampling method, the number of respondents used was 100 respondents. The result is either jointly or individually variable Product Quality, Service, Price and Promotion on purchasing decisions at home eating Star Steak in Karanganyar. The survey results revealed that the price variable is a variable that gives the most influence on purchasing decisions.